A Novel 350 MHz Capacitive Soil Moisture Sensor for Precision Agriculture - Pablo Petrashin; Walter Lancioni; Juan Castagnola (Department of Electrical Engineering ITS and FORTEI, 2025)
This paper presents a novel soil moisture sensor system based on a Colpitts oscillator operating at 350 MHz. The sensor utilizes the variation in capacitance of a sensing capacitor formed by two electrodes inserted into the soil. As soil moisture changes, the dielectric constant of the soil-water mixture also changes, directly affecting the capacitance and thus the oscillation frequency of the Colpitts circuit. This frequency range (150-500 MHz) was specifically chosen to minimize the influence of soil salinity on measurements, as supported by previous research.The sensor design is simple, consisting of readily available and low-cost components such as capacitors, inductors, and only one RF transistor. This simplicity makes the sensor suitable for mass production using standard PCB fabrication techniques. Laboratory tests were conducted using a GW INSTEK GSP-827 spectrum analyzer and a Digital Electronics L/C Meter IIB to calibrate the sensor and validate its performance. The tests demonstrated a strong correlation between oscillation frequency, capacitance, and soil moisture, as evidenced by the data presented.Key advantages of the system include its simplicity, low cost, low energy consumption, and robustness against soil salinity, surpassing the performance of traditional resistive sensors in conductive soils. The sensor offers potential applications in automated irrigation systems and precision agriculture, enabling optimized water usage and improved crop management. Future research directions include linearizing the sensor's response to enhance measurement accuracy, particularly in soils with high conductivity, and developing biodegradable electrodes using materials like beeswax and soy mixtures, balsa wood, or polylactic acid (PLA) to enhance the sensor's sustainability and minimize its environmental impact